2018
DOI: 10.1007/s12664-018-0830-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of transarterial chemoembolization in Egyptian patients with hepatocellular carcinoma and branch portal vein thrombosis

Abstract: TACE seems an alternative option for patients with unrespectable HCC with portal vein thrombosis in patients with good liver function tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…e patients in the hepatic arterial infusion chemotherapy plus radiotherapy group showed remarkably longer median OS rates than those in the sorafenib monotherapy group (p � 0.002) [10]. Several retrospective studies have reported that locoregional therapies, such as transarterial radioembolization and TACE, can affect PVTT progression and intravascular tumors developments [11][12][13]. However, the optimal treatment for HCC patients with MVI is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…e patients in the hepatic arterial infusion chemotherapy plus radiotherapy group showed remarkably longer median OS rates than those in the sorafenib monotherapy group (p � 0.002) [10]. Several retrospective studies have reported that locoregional therapies, such as transarterial radioembolization and TACE, can affect PVTT progression and intravascular tumors developments [11][12][13]. However, the optimal treatment for HCC patients with MVI is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…TACE is recommended for patients with BCLC stage B and should be carried out in a selective manner [1]. An Egyptian study concluded that unresectable HCC with segmental vascular invasion could be treated with TACE with favorable outcome [17]. A proportion of patients in each stage do not fulfill all the criteria for the treatment allocation.…”
Section: Discussionmentioning
confidence: 99%
“…A trial conducted on 30 HCC patients in Egypt used the mRECIST criteria to assess the radiological response. 176 The EASL guidelines recommended evaluating the response to locoregional therapy with mRECIST and systemic therapy with both RECIST and mRECIST criteria. 22 Based on the evidence from the literature, existing guidelines, and clinical trials, all (100%) panelists recommended using the mRECIST Criteria to assess the progression and radiological response after HCC management.…”
Section: Treatment Assessment In Hccmentioning
confidence: 99%